(untitled) (Edma 0-6: Educación Matemática en la Infancia, 2021)
This article presents a research aimed to recognize positions of early childhood future teachers, when analyzing school assignments involving geometry. The activity is developed by children aged 5-6 years old. They are discussed in detail as previous study, responses of three future teachers to a professional task. The results show that it dominates a superficial perspective on how to interpret the actions of children. It also appears some views and interpretations of mathematics teaching. The idea of visualization and conceptualization of patterns like symmetry were found as complex cognitive processes and much unknown.